Gender discrimination in land and property rights and its implication for social work practice in Benin city, Nigeria - Yesufu, Sumaina (My University, 2018)
The United Nations Centre on Housing, Rights and Evictions (COHRE) states that women’s rights to land and property are systematically denied, and over one billion women worldwide have been affected. In Nigeria, although the constitution prohibits all forms of discrimination against women, land and property rights are still determined by the principle of male primogeniture. This study discusses the consequences of gender discrimination on women and their households in relation to land and property rights - and what these portend for social work practice. The aim of the study was to explore gender discrimination in land and property rights, and make recommendations for social work interventions. Qualitative approach was adopted in this design. A total of five key informants, drawn from social workers practicing in various social welfare agencies were interviewed. A total of twenty women constituted the sample size. For the semi-structured interviews, the researcher selected twenty women. For the focus groups discussion, the researcher selected two groups of five women each (ten in total). The focus groups participants were drawn from among the interview participants. The research tools were semi-structured interview schedule and a focus group discussion guide. The researcher analysed the data generated using thematic analysis. The prominent findings were that housing and food insecurity; lack of access to matrimonial property; disinheritance and poverty are among the consequences of gender discrimination on women and their households in relation to land and property rights. Therefore, to effectively solve this problem, social workers in Nigeria, must embrace integrated practice interventions inclusive of other approaches to practice developmental social work. The novelty of the study is that it contributed to a gap relating to our understanding of experiences and perceptions of Nigerian women concerning discrimination in land and property rights. In addition, the study contributed to the advancement of critical social work, and conventional human rights discourse in Nigeria.
A thesis submitted to the Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In fulfillment of the requirements for the Degree of Doctor of Philosophy, 2018
Keywords: Sex discrimination-Nigeria; Land reforms-Nigeria; Sex role-Nigeria